Training for improved performance - Karp, J. R.
Periodization can help your members improve their health and fitness, and give them a potentially more effective way to train. Periodization is a method for structuring training programs using cycles of stimulating loads, maintenance loads, detraining loads and rest to elicit improvements in fitness and performance. Who is periodization for? It wasn't until the middle of the 20th century that the idea of periodizing an athlete's training program was accepted in the U.S. Although periodization is most commonly used for elite athletes to enhance sport performance, it can also be used by your club members who want to get the most out of their exercise program. Much of the information about periodization is anecdotal or conjectural in nature and not yet supported by scientific research. However, many coaches have had great success using periodization to train their athletes. The concept of periodization rests on a sound physiological basis, but it is a concept that is difficult to scientifically scrutinize, since many factors outside of the specific training program can affect how an individual adapts to training. But anecdotal evidence supports that athletes can perform better using the periodization method. History of periodization Periodization divides a training program into stages, an idea that began in Europe in the 1910s, with the focus on sport performance training. It was during that time that athletes began to train year round. But since coaches thought that athletes should not train hard for long periods of time, the need arose for a more structured overall training program. The first attempts at this structure focused on different stages of training, such as general, preparatory and specific. General training was meant to develop the respiratory system and muscular strength; preparatory training aimed to develop strength and endurance by means of different, more sport-specific exercises; and specific training was intended to prepare for a certain sport. In the 1920s and 1930s, the structuring of clearly defined cycles of training began to emerge. Recommendations during that time included that the training process should present a clear alternation of work and rest to form an undulating rhythm of training, that the training should gradually decrease in volume for the same amount of work that it would gain in intensity, and that each specific training period should rest on a generalized base. Training basics Many of your members may ask when they should increase the amount of weight that they're lifting. They may be surprised when you answer, "Try decreasing the weight before making an increase." The decrease functions as an active rest period, resulting in a greater state of readiness to handle a higher training load. Including rest periods in a training program is especially beneficial when training with high intensity and/or high volume. Improvements in fitness (as measured by increased strength or endurance) occur during the rest period, not during the training itself. Positive physiological adaptations to training result from correctly-timed alternations between stress and regeneration. Negative adaptation occurs because of too great a stimulus and/or too little regeneration. After a controlled training overload, there is a period when the body adapts to the overload and works to reestablish homeostasis. Essentially, the body overcompensates for its adaptation so that the same stimulus, if reintroduced to the body, will not cause the same disruption of homeostasis. After it has adapted to the overload, the body is capable of doing more work for an equivalent homeostatic displacement. This is called over or supercompensation. The basic aim of training, therefore, is to apply a series of stimuli that will displace the homeostasis of the body's functional systems and provide a stimulus for adaptation and supercompensation. If the training stimulus is too small in either intensity or duration, little or no adaptation will take place. However, if the stress is too severe, the adaptation will be delayed or even prevented. How periodization works With the periodization training method, a year of training is divided into major periods called macrocycles, which last about three to four months. The macrocycles are further divided into mesocycles, which typically last three to four weeks, and microcycles, which are typically one week. Thus, three to four microcycles make up one mesocycle, and three to four mesocycles make up one macrocycle. Figure 1 illustrates the periodization concept using three-week mesocycles, with each bar on the graph representing one microcycle, or one week of training. During a three-week mesocycle, the first two microcycles contain stimulating loads when the body is overloaded by an increase in training volume or intensity. Fatigue accumulates from the heavy training loads. These two microcycles are followed by a short detraining, or restoration, microcycle. During this cycle, which is typically one week long, the level of fatigue decreases, preparing the body to handle the upcoming new exercise stress. Rest is a very important component of the overall training program, since it is during rest that the body's adaptations to exercise occur. When individuals step off of a treadmill or walk out of the gym after a strength-training workout, they are weaker, not stronger. How much weaker depends on the severity of the exercise stress. If there is not enough rest between workouts or mesocycles, fatigue will accumulate and no further improvements in fitness will take place. The greatest adaptation to a stimulus occurs when muscles are recovered from previous training. Therefore, a restoration microcycle should precede an increase in either exercise intensity or volume. If a four-week mesocycle is used, the third microcycle can be used as a "crash" microcycle, in which the body is overloaded to a greater degree than the two previous cycles. Then the fourth cycle becomes the restoration cycle, as illustrated in Figure 2. As physical fitness improves, each new mesocycle should involve greater average training loads than the cycle just completed. During the restoration cycle, which is the final week of each mesocycle, the volume and intensity are decreased to eliminate the fatigue that has accumulated during the previous weeks of training. A key component to periodization is the systemization of the training stimulus. The training volume or intensity should not be increased arbitrarily, but in a systematic way, since exceeding a certain training load in a given time frame will increase fatigue and lead to overtraining. Systemization, therefore, governs the total load used during a single training session or microcycle, as well as the frequency of training sessions. Variation of training loads is another important component of periodization. A programmed variation of volume and intensity for strength training may produce superior results compared to a program that does not vary the training stimulus. Different phases of training result in various types of stress and may affect different functional systems in the body. Therefore, the response to the applied stress may take different forms during the various training phases. The effects of high-intensity training, for example, differ from those of high-volume training. This is important to remember when monitoring an individual's training effect and recovery.